2022
DOI: 10.1002/mabi.202200247
|View full text |Cite
|
Sign up to set email alerts
|

The Relation Between Protein Adsorption and Hemocompatibility of Antifouling Polymer Brushes

Abstract: Whenever an artificial surface comes into contact with blood, proteins are rapidly adsorbed onto its surface. This phenomenon, termed fouling, is then followed by a series of undesired reactions involving activation of complement or the coagulation cascade and adhesion of leukocytes and platelets leading to thrombus formation. Thus, considerable efforts are directed towards the preparation of fouling-resistant surfaces with the best possible hemocompatibility. Herein, a comprehensive hemocompatibility study af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 70 publications
0
13
0
Order By: Relevance
“…The formation of biofouling happening in complex fluids such as saliva, blood, and tissue medium, is usually composed of three stages: (i) Nonspecific adsorption of biomacromolecules such as protein; (ii) Sparse adhesion of bacteria or body cells; (iii) Formation of biofilm. [211][212][213][214][215] The construction of the hydrated polymer brush layer, which mainly depends on surface hydrophilicity, is a conventional strategy to prevent initial protein adsorption, followed by reduced cell or bacteria adhesion. [216][217][218] The hydration layer can be formed by the interaction between hydrophilic groups and water, which presents stereoscopic repulsion to reduce nonspecific adsorption.…”
Section: Antifoulingmentioning
confidence: 99%
See 1 more Smart Citation
“…The formation of biofouling happening in complex fluids such as saliva, blood, and tissue medium, is usually composed of three stages: (i) Nonspecific adsorption of biomacromolecules such as protein; (ii) Sparse adhesion of bacteria or body cells; (iii) Formation of biofilm. [211][212][213][214][215] The construction of the hydrated polymer brush layer, which mainly depends on surface hydrophilicity, is a conventional strategy to prevent initial protein adsorption, followed by reduced cell or bacteria adhesion. [216][217][218] The hydration layer can be formed by the interaction between hydrophilic groups and water, which presents stereoscopic repulsion to reduce nonspecific adsorption.…”
Section: Antifoulingmentioning
confidence: 99%
“…Hence inherently antifouling properties of artificial surfaces are required to prevent the settlement of bacteria and body cells. The formation of biofouling happening in complex fluids such as saliva, blood, and tissue medium, is usually composed of three stages: (i) Nonspecific adsorption of biomacromolecules such as protein; (ii) Sparse adhesion of bacteria or body cells; (iii) Formation of biofilm [211–215] . The construction of the hydrated polymer brush layer, which mainly depends on surface hydrophilicity, is a conventional strategy to prevent initial protein adsorption, followed by reduced cell or bacteria adhesion [216–218] .…”
Section: Bioapplications Of Polymer Brushesmentioning
confidence: 99%
“…In addition, when a protein adsorption layer is formed, it becomes resistant to oxygen permeation, and the oxygen supply to the cornea can be reduced. Previous studies have reported that hydrophilic polymer-grafted surfaces effectively reduce protein adsorption. , Among the hydrophilic polymers that have been studied, the MPC polymers is recognized by many review papers to have a particularly excellent effect of inhibiting protein adsorption. ,,, Because the contact lens resides within the tear film, the aqueous layer that should be covered by the anterior lipid layer is much thinner. It also acts as a tear film, clearing it: the smooth surface of the eye along which the eyelid moves during blinking.…”
Section: Antifouling Properties On Biomimetic Silicone Hydrogel Conta...mentioning
confidence: 99%
“…Moreover, poly(2-hydroxyethyl methacrylate) or poly(vinyl alcohol) (PVA) can activate the complement system. 97,98 When poly(ethylene oxide) (PEO), which is a popular injectable water-soluble polymer, is covalently grafted on the surface of substrate, protein adsorption is temporarily impeded. This is because the excluded volume effect and the microscopic motions during grafting of the water-soluble polymer onto the surface prevent the protein from approaching.…”
Section: Construction Of Biointerfacesmentioning
confidence: 99%